Clinical and Histopathologic Ocular Findings in Disseminated Mycobacterium chimaera Infection after Cardiothoracic Surgery - Zweifel, Sandrine A.; Mihic-Probst, Daniela; Curcio, Christine A.; Barthelmes, Daniel; Thielken, Andrea; Keller, Peter M.; Hasse, Barbara; Böni, Christian (Ophthalmology (Rochester, Minn.), 2017)
To investigate and characterize clinical and histopathologic ocular findings in patients with disseminated infection with Mycobacterium chimaera, a slow-growing nontuberculous mycobacterium (NTM), subsequent to cardiothoracic surgery. Observational case series. Five white patients (10 eyes). Analysis of clinical ocular findings, including visual acuity, slit-lamp biomicroscopy, spectral-domain optical coherence tomography (SD OCT), fundus autofluorescence (FAF), and fluorescein angiography/indocyanine green (ICG) angiography findings, of patients with a disseminated M. chimaera infection. Biomicroscopic and multimodal imaging findings were compared with the histopathology of 1 patient. Clinical and histopathologic ocular findings of M. chimaera. The mean age of the 5 male patients, diagnosed with endocarditis or aortic graft infection, was 57.8 years. Clinical ocular findings included anterior and intermediate uveitis, optic disc swelling, and white-yellowish choroidal lesions. Multifocal choroidal lesions were observed bilaterally in all patients and were hyperfluorescent on fluorescein angiography, hypofluorescent on ICG angiography, and correlated with choroidal lesions on SD OCT. The extent of choroidal lesions varied from few in 2 patients to widespread miliary lesions in 3 patients leading to localized choroidal thickening with elevation of the overlying retinal layers. Spectral-domain optical coherence tomography through regressing lesions revealed altered outer retinal layers and choroidal hypertransmission. The ocular findings were correlated with the course of the systemic disease. Patients with few choroidal lesions had a favorable outcome, whereas all patients with widespread chorioretinitis died of systemic complications of M. chimaera infection despite long-term targeted antimicrobial therapy. Ocular tissue was obtained from 1 patient at autopsy. Necropsy of 2 eyes of 1 patient revealed prominent granulomatous lymphohistiocytic choroiditis with giant cells. M. chimaera infection subsequent to cardiothoracic surgery is a novel entity that has been recently described. It involves multiple organ systems and can cause life-threatening disseminated disease. The ocular manifestations documented using multimodal imaging allow us to use the eye as a window to the systemic infection.